1963
DOI: 10.1111/j.1570-7458.1963.tb00603.x
|View full text |Cite
|
Sign up to set email alerts
|

ON THE VISUAL ORIENTATION OF MOSQUITOES IN THEIR SEARCH OF RESTING PLACES1

Abstract: Tests with unfed females, bloodfed females and such with fullgrown ovaries of Anopheles albimanus, A. quadrimaculatus, A. aztecus, A. punctipennis, Culex quinquefasciatus and Aedes aegypti were made by introducing them into large drum‐like boxes of transparent plastic, in which one circular side has been covered with papers of different shades or of contrasting patterns of black and white. In general the mosquitoes preferred to settle on the black areas or on the black parts of the different patterns. However … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…These authors found a correlation between the amount of light reflected by the painted surface and its attractiveness to flies, the lighter colours being less attractive than the darker colours. HECHT (1963) found the same tendency in experiments with paper of different shades covering the bottom of a test box; more flies were counted on grey than on white paper, and even more on black. Other experiments indicate that there is a special attraction to red colours.…”
mentioning
confidence: 53%
“…These authors found a correlation between the amount of light reflected by the painted surface and its attractiveness to flies, the lighter colours being less attractive than the darker colours. HECHT (1963) found the same tendency in experiments with paper of different shades covering the bottom of a test box; more flies were counted on grey than on white paper, and even more on black. Other experiments indicate that there is a special attraction to red colours.…”
mentioning
confidence: 53%
“…Here, we show that black cotton cloths impregnated with fungal conidia, when deployed in the presence of mosquitoes, reduced the survival of female A. aegypti . Black surfaces are known to attract a range of mosquito species (Hecht and Hernandez‐Corzo ), although other studies have shown that stationary objects of low reflectance and solid colour were the most attractive to male and female A. aegypti (Muir et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we tested a simple and cheap approach for controlling adult A. aegypti based on the fact that black surfaces attract a range of mosquito species including A. aegypti (Hecht & Hernandez‐Corzo, ). The PET traps were first tested with adhesive films to compare the capture rates with and without the presence of black cloths.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we tested a simple and cheap approach for controlling adult A. aegypti based on the fact that black surfaces attract a range of mosquito species including A. aegypti (Hecht & Hernandez-Corzo, 1963).…”
Section: Discussionmentioning
confidence: 99%